Evaluation of the efficiency of public support for cluster organizations in the Czech Republic - Miroslav Žižka; Vladimíra Hovorková Valentová; Natalie Pelloneová; Eva Štichhauerová (DANUBE: Law, Economics and Social Issues Review, 2019)
The research presented in the paper aims to find out whether the public support (subsidies) received by cluster organizations for their development and activities is efficient. That means whether the state receives a return on investment in the form of increased revenues to public budgets. The research was conducted on a sample of seven cluster organizations that include the following sectors: furniture, packaging and textile production, engineering, the automotive industry, IT and nanotechnology. For each cluster organization, the data on subsidies was drawn from the moment of their establishment until 2017. At the same time, a list of the cluster member organizations was drawn up, with financial data being collected only for business entities. For each enterprise, information about paid corporate income tax, income tax on employment from employee wages, and social and health insurance paid by the companies and their employees was collected. In the next phase, increases in taxes and insurances were monitored and compared to the year in which the cluster organization drew a subsidy for the first time. Subsequently, the public support efficiency rate and payback period were calculated. The research results show that public support for cluster organizations is efficient, with a relatively short payback period.
Keywords: 330; Cluster; Cluster Organization; Cluster Initiative; Public Support; Efficiency; Payback Period